SISTEM PRODUKSI PETERNAKAN SAPI POTONG BERBASIS SUMBERDAYA LOKAL PADA PROGRAM SARJANA MEMBANGUN DESA (SMD)( LIVESTOCK PRODUCTION SYSTEM OF BEEF CATLE BASED ON LOCAL RESOURCES AT THE PROGRAM OF SARJANA MEMBANGUN DESA (SMD)) - Sodiq , Akhmad; , Munadi; Purbojo, Satrio Widhi (Pembangunan Pedesaan, 2010)
The objectives of this study were to describe the profile of livestock production system on beef cattle under local resources base. Livestock On-Farm Trials was applied in this study by involved 21 farmer groups of beef cattle under program of Sarjana Membangun Desa. The program distributed at 8 regencies with the various agro ecosystems (low-middle-land, up-land, forest-margin, and rice-base). Descriptive analysis was applied in this study. This study demonstrated that beef cattle production closely integrated to the overall crop farming based on the condition of agro ecosystems. A number of local resources and by-products of agriculture and agro industry made the most of feeding practice. Crop-Livestock-System needed to be developed in the framework of sustainable development.